The legal construction of personal work relations - Freedland, M. R. (Mark Robert); Kountouris, Nicola (Oxford : Oxford University Press, 2011)
This text explores the framework of European employment law through an analysis of domestic national laws and their interaction with EU law. It focuses on understanding current developments in the law's picture of working relationships, and exploring the potential for further harmonisation of employment law.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 17, 2012).
Keywords: Labor laws and legislation -- European Union countries